The Role of Kidney Biopsy in Fabry Disease - Irene Capelli; Laura Martano; Gian Marco Berti; Gisella Vischini; Sarah Lerario; Vincenzo Donadio; Alex Incensi; Valeria Aiello; Francesca Ciurli; Benedetta Fabbrizio; Stefano Chilotti; Renzo Mignani; et al. (Biomedicines)
Fabry disease (FD) is a rare X-linked lysosomal storage disorder caused by mutations in the GLA gene, leading to α-galactosidase A deficiency and subsequent accumulation of glycosphingolipids, including globotriaosylceramide (Gb3) and globotriaosylsphingosine (lyso-Gb3), in multiple organs. This accumulation can result in multisystemic disease and life-threatening complications. FD presents with a broad phenotypic spectrum, ranging from the classic form, with early and severe symptoms, to a later-onset form with variable manifestations. The severity of the disease in females is more variable due to X-chromosome inactivation (XCI). Renal involvement is a key feature, and kidney biopsy remains a valuable tool for diagnosing FD and assessing the extent of nephropathy. Although molecular genetic testing is the gold standard for diagnosis, kidney biopsy aids in confirming renal involvement, detecting coexisting conditions, and determining the pathogenicity of variants of uncertain significance (VUSs). Moreover, kidney biopsy can serve as a prognostic tool by identifying early markers of nephropathy, such as foot process effacement and glomerular sclerosis, which predict disease progression. Emerging technologies, including machine learning, offer the potential to enhance the analysis of renal histology, improving diagnostic accuracy and patient stratification. Despite the challenges posed by overlapping diseases and potential misdiagnoses, kidney biopsy remains an essential component of FD diagnosis and management, facilitating early detection, the monitoring of disease progression, and the evaluation of therapeutic responses.